EXTENT OF DAMAGE TO COCONUT PALMS CAUSED BY SUPER CYCLONE IN ORISSA AND PATTERN OF THEIR RECOVERY - D.K. Dash; D.P. Ray; H. Hameed Khan (International Coconut Community, 2002)
During the Super cyclone (October, 1999) in the coastal districts of Orissa, 26,836 hectares of coconut garden having 46,96,300 palms were severely affected. A survey of affected palms in the selected villages classified the palms as (i) uprooted (11.3 percent) (ii) palms with complete crown damage (23.3 percent) (iii) palms with severe damage to the crown (32 percent) and (iv) palms with partial crown damage (34 percent). The affected palms lost most of their valuable leaves and spadices in their varying stages of development. The recovery of palms started after 2 months of damage in the form of production of new leaves. The spadices production started after 4-5 months of damage. The number of palms entered the fresh reproductive stage is of low percent, which may lead to in 2-3 years delay in nut production by the palm. Regular manuring with organics and inorganics, adequate plant protection are suggested to rejuvenate the palms.